DISCUSSION OF SUFISM IN DAGESTAN IN THE HISTORICAL RETROSPECTIVE - Sihaliev, Samil' Sihalievic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper analyses the discussion of Sufism between the representative of different trends in Dagestan – Sufi sheikhs, on the one side, and Islamic reformers on the other. The introduction part provides a brief historical excursus on the history of Sufism dissemination in Dagestan. Initially, before the spread of the ideas of Muslim reformism in Dagestan and even in parallel with the movement of reformism, the discussion about the legitimacy of certain practices took place within different groups of Sufi communities. At the end of the imperial period, the reformers, better known in the scientific literature as the Jadids, joined the discussion. It is noteworthy that among the reformers, the attitude towards Sufism and Sufis was not the same. One group of Jadids considered Sufism to be a legitimate trend in Islam, criticizing in the pages of the Islamic press only contemporary Dagestan Sufi sheikhs. Another group of reformers went further and did not recognize the legitimacy of Sufism at all. This controversy did not end in the early Soviet period, and survived to this day. In the post-Soviet period, the same rhetoric about the illegitimacy of Sufism as a trend, which did not exist during the time of the Prophet Muhammad and the first generation after him, was picked up by modern Salafists. In turn, Sufi sheikhs of both the early Soviet and post-Soviet periods also wrote works refuting the views of their opponents. Despite the common rhetoric of the early Soviet Jadids and post-Soviet Salafists, there is still no continuity of traditions between them. The paper is based on the analysis of original Arabic sources, including manuscripts and articles in the local press, many of which have been introduced into scientific circulation for the first time.